Interfacial and Rheological Properties of Oil-In-Water Emulsions as Affected by Egg Yolk From Different Sources - Wan Ibadullah, Wan Zunairah (2008)
Hen egg yolk is an essential ingredient for the preparation of a large variety food emulsions, such as mayonnaises, salad dressings and creams. The preparation and long-term stability of this kind of food are influenced by the solution pH. However, the emulsifying properties of duck and goose egg yolk remain unknown as they have not been clearly documented. In this study, the emulsion properties (droplet size, solubility, and viscosity), interface attributes (interfacial protein concentration, percentage of adsorbed proteins, SDS-Page profiles of adsorbed proteins and interfacial tension) and rheological properties (thixotropic behavior) of oil-in-water emulsions prepared with hen, duck and goose egg yolks were examined. These features were observed at three different pHs (3, 6 and 9). Results showed that pH 6 provided the best conditions for preparing emulsion using the three types of egg yolks. The droplet size of goose egg yolk emulsions at pH 6 was the smallest than other types of egg yolk at all pH levels. The protein solubility was lower at pH 6 for all types of egg yolk emulsions. The viscosities of hen, duck and goose egg yolk emulsions at pH 6 were higher than those at pH 3 and 9. In the pH range studied, the interface attributes were better at pH 6 for all types of egg yolks. The interfacial protein concentration was higher at pH 6 for the three types of yolks (1.70 mg m⁻², 1.74 mg m⁻² and 1.98 mg m⁻², respectively) than at pH 3 and pH 9. At pH 6, most of the proteins from the three yolks were adsorbed at the interface and the interfacial tension at steady-state was lower (10 mN m⁻¹, 13.98 mN m⁻¹ and, 8.37 mN m⁻¹ respectively) than at pH 3 or pH 9. At pH 3, proteins at the interface were mainly phosvitin, and at pH 9, some apoproteins of HDL and LDL were detected. The pH modulates the composition of yolk proteins at the interface, mainly by modifying the net charge of the proteins causing their repulsion or dimerization. The micrographic observation showed that the oil droplets were more uniform at pH 6 than those at pH 3 and 9 for all types of egg yolk emulsions. At pH 6, all of the egg yolk emulsions exhibited thixotropic shear thinning behavior under steady shear test. Emulsions produced at pH 3 and 9 exhibited closely the Newtonian behavior. These results suggested that hen, duck and goose egg yolk are able to provide stabilizing effects at pH 6. This study shows a good potential for goose and duck egg yolk to be used as an alternative emulsifying agent in the food industry.